Knowledge, Attitude and Practices (KAP) of Mothers toward Infant and Young Child Feeding in Primary Health Care (PHC) Centers, Erbil City. - Norhan Shaker; Kareema Hussein; Sawsan AL-Azzawi (Kufa Journal for Nursing Sciences)
Background: Improving infant and young child feeding practices in children birth–23 months of age is therefore critical to improved nutrition, health, development of children and, ultimately and impact child survival.